Analisis Tata Keuangan Daerah Provinsi Bangka Belitung Tahun Anggaran 2008-2013 - Moh. Benny Alexandri (Jurnal Study and Management Research, 2014)
The purpose of this study was to determine financial governance of Bangka Belitung Province Indonesia. The method used in this studywas descriptiveanalysis. The sample used in this study were the Province Financial Statements year 2008-2013. The purpose of this study were (1) To Knowcondition of Kep .Bangka Belitung Province year.2008 - 2013. (2) To Know the Projections 2013-2023 .of Province Financial Condition (3) To Determine financial strategy of Kep Bangka Belitung Province. The results of this study of Kep.Bangka Belitung is good enough which demonstrated by some indicators, such as the Regional Financial Independence Analysis was results less , Regions Financial Dependency Ratio was High result , Fiscal Decentralization ratio was enough results , ratio with the results of Highly Effective Effectiveness and Efficiency Ratio was Inefficient . Financial Projections Kep Bangka Belitung shows the condition of PAD is more stable and tends to increase with the proportion of about 10 % of APBD . Financial governance strategy can be described by quadrant II in Regional Capability Index which illustrates that KepBangka Belitung Provincewere good, and has the potential for increasing revenue.